Sintering and open die forging process for P/M titanium alloy with additions of trace amount of erbium. (July 2015) - Lou, J.; Gabbitas, B.; Raynova, S.; Yang, F.
<x content-type="archive" xml:space="preserve">Abstract</x> Er powder with a very large particle size was added to Ti metal and Ti–6Al–4V alloy to achieve a supersolidus liquid sintering effect. However, instead of promoting sintering and homogenisation, very big worm-like voids were created by a substantial Er–Ti liquid phase. Such voids were surrounded by Er segregation and made tensile testing of a Ti–Er alloy impossible. An open die forging process was then employed to diminish these pores and homogenise the Er distribution. Fine Er spots or acicular textures were found in the matrix, but some Er segregation still persisted. The material is weakened by segregation. Good mechanical properties are obtained when the testpieces have reduced levels of Er segregation. Further work will be focused on the homogenisation of Er.